Contemporary Pesantren (A Case Study of Pesantren Baitul Hikmah Yogyakarta) - Setyabudi, Muhammad Nur Prabowo (Pusat Studi Pesantren dan Pemberdayaan Masyarakat, LPPM, Universitas Brawijaya, 2019)
This article describes three points about Pesantren modernization development. First: pesantren as Islamic educational institution that has an old tradition in Indonesia has more diversification and differentiation today.Â One of the forms of that diversification is pesantren becoming academic sub-culture that supports scientific works. Second: this category is very affecting the Kyai role as the leader of pesantren and having academic capacity and reputation at the same time at University in some certain discipline of science. The author takes Pesantren Baitul Hikmah in Yogyakarta as the sample. In this part, the author gives the description of Pesantren Baitul Hikmah's educational process, advantages, and its curriculum. Pesantren Baitul Hikmah has the advance in the field of interpretation of the Qur'an and Hermeneutic as its device. Third, the author attempts to use the significance of hermeneutic analysis as developed at the pesantren for developing interpretative religious research.Keywords: Pesantren; Academic Sub-culture; Hermeneutics; Kyai